A ciência na imprensa paraense em 130 anos: um estudo de três grandes jornais diários - CARVALHO, Vanessa Brasil de (Universidade Federal do Pará, 2013)
This research presents an exploratory study in order to recognize the scenario on covering scientific topics in newspapers of Pará, therefore, our attention was focused on the analysis of three three important newspapers paraenses over 130 years: A Província do Pará (1876-2002), Folha do Norte (1896-1974) and O Liberal (1946-current). To select the texts that report about science, we investigate the daily editions of January and July every ten years in those newspapers, from 1876 to 2006. It was made adaptations in the protocol of Rede Ibero-Americana de Monitoramento e Capacitação em Jornalismo Científico – for television analyses – in order to allow the research with newspapers. The protocol is based on the concept of content analysis and allowed the characterization and systematization of 496 texts with scientific issues that we found using the chosen method. We identified many information as the date of publication of the text, the presence of headlines and front page of the newspaper, the journalistic genre of texts, the predominant field of knowledge, the visuals used, the frames, the contextualization of science, the explanations in scientific terms, the benefits and harms and the promises and risks of science, scientific and not scientific controversies, sources and voices, and places of research and researchers in those selected texts. Our research showed that science was already part of the agenda of newspapers in Pará by the end of the nineteenth century, but gained more space in the second half of the twentieth century. There was a strong emphasis on scientific issues related to health, despite the space research have also had an important presence. We also observed significant contextualization and explanations of scientific terms. Overall, the science was published from its "positive" side, showing its benefits, and with an emphasis on scientific discoveries. On the other hand, we registered few discussions of controversies. The visuals were also rare. Most of the sources and voices were identified as scientists or research institutions, and most of them were men. There was a balance between research and researchers from Brazil and those from outside the country. A Província do Pará highlighted themes of engineering and technology (although health was predominant) and gave a differentiated emphasis in sources and voices unscientific. Folha do Norte published longer texts with much context. And O Liberal emphasized issues of medicine and the humanities, and also was the only journal that has put more focus on Brazilian and paraense research and researchers.